Detection and molecular characterization of phytoplasma affecting vegetables in Eastern Visayas, Philippines - Borines, Lucia M.; Nuñez, Joy Adeline C.; Duero, Nickie D.; Sagarino-Borines, Rezel; Gerona, Reny G. (Annals of Tropical Research, 2020)
Phytoplasma-like diseases were observed affecting bitter gourd, Loofah, string bean, “Baguio” bean, cucumber, and tomato in Eastern Visayas, Philippines. The infected vegetables commonly show little leaf/witches’ broom symptoms. The study aimed to detect and confirm phytoplasmas presence in these vegetables through PCR and nest PCR assays using universal primers, electron microscopy, and 16srDNA sequence analysis. Loofah little leaf had the highest prevalence (50% of the surveyed farms), followed by bitter gourd (45%) and string beans (31%). The disease had an approximate mean incidence of 27% for bitter gourd, 38.0% for Loofah, and 42.5% for string bean, in farms where plants showed infections. Electron micrographs of bitter gourd and Loofah samples showed phytoplasma cells in the phloem sieve tubes. Nest PCR assays using R1 6F2n/R16R2 primer linked to phytoplasmal6srDNA amplified a 1.25Kb band in the majority of DNA samples. rDNA sequence analysis using Blastn showed that phytoplasmas in bitter gourd, Loofah, and one cucumber samples shared 98-99% identity with Loofah’s reference gene phytoplasma clones. More than one phytoplasma strain infected the vegetables based on Rsai enzyme digestion and phylogenetic analysis.